Comparative social demography, livelihood diversification and land tenure among the Maasai of Kenya and Tanzania - Nkedianye, David K.; Ogutu, Joseph O.; Said, Mohammed Y.; Kifugo, Shem C.; Leeuw, Jan de; Gardingen, Paul van; Reid, Robin S. (Springer, 2020)
We analyse social demography, livelihood diversification and land tenure among the Maasai people inhabiting Kenya (three sites) and Tanzania (one site) with contrasting land tenure policies. In Kenya, land was communally owned in the rural Amboseli, fully privatized in the peri-urban Kitengela in Athi-Kaputiei and partially privatized and communally owned in the rural Maasai Mara. In Tanzania, the government owned the land but granted user rights to local villages in rural Simanjiro in Tarangire-Manyara. We interviewed 100 households per site from May to July 2006. There were regional distinctions in social demography, livelihood diversification, hiring herding labour and settlement arrangements, portraying differential transition away from traditional pastoral Maasai society. The transition is most advanced in Kitengela located near Nairobi City, where privatization of land tenure in the 1980s triggered land sub-division, unprecedented land fragmentation and large-scale collapse of the commons, pastoralism and conservation. Land privatization and sub-division in Maasai Mara and Amboseli started in 2000s and were followed similarly by unprecedented fragmentation through fences and accelerated collapse of the commons, pastoralism and conservation, except where wildlife conservancies were later established. We found several differences at the household, regional and national levels. The average age of household heads was lower in Maasai Mara and Amboseli than in Kitengela and Simanjiro. The average number of wives per male household head was lowest in Kitengela, intermediate in Mara and Amboseli and highest in Simanjiro. Correspondingly, the mean number of children per family was lowest in Kitengela, intermediate in Mara and Amboseli and highest in Simanjiro. Household heads were more educated closer to urban centres. Household heads without formal education were thus most common in Amboseli, intermediate in Mara and Simanjiro and fewest in Kitengela. Livelihood diversification was marked in all the sites. Notably, cultivation was widespread and most of those interviewed were interested in crop cultivation. The average number of acres cultivated per household was far higher in Simanjiro than in all the other sites. The mean number of hired herders per household was higher in Kitengela, with the highest number of children enrolled in schools, than in the Mara, Amboseli or Simanjiro. The average number of households per settlement was highest in the Mara, intermediate in Amboseli and Simanjiro and lowest in Kitengela. The marked regional variation in social demography, livelihood diversification and land tenurial arrangements reflects underlying variation in proximity to urban centres, agro-climatological and national developmental and policy environments.